Water for people, water for life : a joint report by the twenty-three UN agencies concerned with freshwater - World Water Assessment Programme (United Nations) ([New York] : Berghahn Books, 2003)
A comprehensive assessment of the state of the world's freshwater resources, based on the collective input of twenty-three United Nations agencies and convention secretariats.
Includes bibliographical references and index.
Choice.
Adult
Keywords: Water quality management; Water resources development; Water-supply -- Management; Water resources development; Water supply -- Management; Water -- Analysis; Water -- Quality control